The efficacy of TKIs in treatment of human primary small cell lung cancer xenograft model in vivo - Yu-Hua, Zhang; Liang, Sun; Bin, Liu; Guo-Qiang, L I (Zhongguo ying yong sheng li xue za zhi, 2016)
To study the treatmaient of non-small cell lung cancer, we established the HU-Prim allograft transplantation tumor model. The fresh tumor samples were transplanted in the right scapular subcutaneous layer of the severe combined immunodeficient Non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice. The pathological features of the tumors were observed. Nonnecrotic tissue was inoculated subcutaneously into the right axillary. When the tumor in burdened rat grew approximately 100 mm , according to the tumor size all the animals were divided into the following four groups, eight rats in each group:solvent control group, gefitinib group (100 mg/kg), erlotinib group (50 mg/kg), afatinib group (20 mg/kg). Aniamals were treated with drugs by intragastric (i.g.) administrated, once daily, for consecutively 14 days. Measure the tumor size 2-3 times every week. HuPrime1-NSCLC mutant sensitive xenograft model research data showed that reversible tyrosine kinase inhibitors gefitinib, erlotinib and irreversibl